Shorted Rectangular Microstrip Antenna for Dual-band Operation - Singh A.K.; Meshram M.K. (My University, 2025)
Paper presents the study of shorted rectangular microstrip antenna for dual band operation. The analysis have been carried out by varying the shorting-pin position from edge to center of the patch, such an antenna provides tunable frequency ratio of about 2.91 to 2.2 for the two operating frequencies. When the shorting-pin position is close to center or at the center of the patch, a single resonant frequency is observed. Theoretical and experimental results are in good agreement. © 2006 IEEE